Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve this system of equations, we follow a step-by-step algebraic approach:
### Step 1: Write down the given equations.
We have two equations:
1. [tex]\( \frac{m}{n} = \frac{6}{11} \)[/tex]
2. [tex]\( n - m = 155 \)[/tex]
### Step 2: Express [tex]\(m\)[/tex] in terms of [tex]\(n\)[/tex] from the first equation.
From the first equation:
[tex]\[ \frac{m}{n} = \frac{6}{11} \][/tex]
We can cross-multiply to eliminate the fraction:
[tex]\[ 11m = 6n \][/tex]
This rearranges to:
[tex]\[ m = \frac{6}{11}n \][/tex]
### Step 3: Substitute [tex]\(m\)[/tex] from Step 2 into the second equation.
The second equation is:
[tex]\[ n - m = 155 \][/tex]
Substitute [tex]\( m = \frac{6}{11}n \)[/tex] into this equation:
[tex]\[ n - \frac{6}{11}n = 155 \][/tex]
### Step 4: Simplify the equation to find [tex]\(n\)[/tex].
Combine like terms:
[tex]\[ \frac{11n}{11} - \frac{6n}{11} = 155 \][/tex]
[tex]\[ \frac{5n}{11} = 155 \][/tex]
Solve for [tex]\(n\)[/tex]:
[tex]\[ 5n = 155 \times 11 \][/tex]
[tex]\[ 5n = 1705 \][/tex]
[tex]\[ n = \frac{1705}{5} \][/tex]
[tex]\[ n = 341 \][/tex]
### Step 5: Substitute [tex]\(n\)[/tex] back into the equation for [tex]\(m\)[/tex].
We found that [tex]\( n = 341 \)[/tex]. Now, use the expression [tex]\( m = \frac{6}{11}n \)[/tex]:
[tex]\[ m = \frac{6}{11} \times 341 \][/tex]
[tex]\[ m = 186 \][/tex]
### Conclusion
The values of [tex]\(m\)[/tex] and [tex]\(n\)[/tex] that satisfy both equations are:
[tex]\[ m = 186 \][/tex]
[tex]\[ n = 341 \][/tex]
### Step 1: Write down the given equations.
We have two equations:
1. [tex]\( \frac{m}{n} = \frac{6}{11} \)[/tex]
2. [tex]\( n - m = 155 \)[/tex]
### Step 2: Express [tex]\(m\)[/tex] in terms of [tex]\(n\)[/tex] from the first equation.
From the first equation:
[tex]\[ \frac{m}{n} = \frac{6}{11} \][/tex]
We can cross-multiply to eliminate the fraction:
[tex]\[ 11m = 6n \][/tex]
This rearranges to:
[tex]\[ m = \frac{6}{11}n \][/tex]
### Step 3: Substitute [tex]\(m\)[/tex] from Step 2 into the second equation.
The second equation is:
[tex]\[ n - m = 155 \][/tex]
Substitute [tex]\( m = \frac{6}{11}n \)[/tex] into this equation:
[tex]\[ n - \frac{6}{11}n = 155 \][/tex]
### Step 4: Simplify the equation to find [tex]\(n\)[/tex].
Combine like terms:
[tex]\[ \frac{11n}{11} - \frac{6n}{11} = 155 \][/tex]
[tex]\[ \frac{5n}{11} = 155 \][/tex]
Solve for [tex]\(n\)[/tex]:
[tex]\[ 5n = 155 \times 11 \][/tex]
[tex]\[ 5n = 1705 \][/tex]
[tex]\[ n = \frac{1705}{5} \][/tex]
[tex]\[ n = 341 \][/tex]
### Step 5: Substitute [tex]\(n\)[/tex] back into the equation for [tex]\(m\)[/tex].
We found that [tex]\( n = 341 \)[/tex]. Now, use the expression [tex]\( m = \frac{6}{11}n \)[/tex]:
[tex]\[ m = \frac{6}{11} \times 341 \][/tex]
[tex]\[ m = 186 \][/tex]
### Conclusion
The values of [tex]\(m\)[/tex] and [tex]\(n\)[/tex] that satisfy both equations are:
[tex]\[ m = 186 \][/tex]
[tex]\[ n = 341 \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.